Mina Karadžić Vukomanović (1828–1894), A Selective Bibliography (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
After a short introductory bibliographic citation, the work gives biographical data on Mina Karadžić-Vukomanović and especially on her literary production. The largest part of the work is her selective bibliography which is divided into three different sections: Mina Karadžić-Vukomanović Works, Works About Mina Karadžić-Vukomanović and Non-Book Materials.
Keywords: bibliography; Mina Karadžić-Vukomanović